Kandungan Logam Berat Pb, Cd, Cu, Zn, Ni dan Senyawa Polisiklik Aromatik Hdrokarbon (PAH) dalam Sedimen di Teluk Jakarta - Edward Edward; Khosanah Munawir; Deny Yogaswara; Dede Falahuddin; Agus Kusnadi; Teddy Triandiza; Helfinalis Helfinalis; Ita Wulandari; Lestari S Lestari S; Rosmi N Pesilette (Jurnal Sumberdaya Akuatik Indopasifik, 2021)
Research on heavy metals content Pb, Cd, Cu, Zn, Ni and Polycyclic Aromatic Hydrocarbon (PAH) in sediment were carried out in Jakarta Bay in Mei 2016. The purpose of this research is to known the degree of heavy metals pollution Pb, Cd, Cu, Zn, Ni and PAH in sediment in its relation to marine biotas protection. Research location were Ancol/Marunda waters, Gembong Estuary and Pari Island waters. Sediment samples analyzed using Atomic Absorption Spectrophotometer (AAS) and Gas Chromatography. The results showed that according to contamination factor values, geo accumulation and load pollution index, sediment in Jakarta Bay including to low contamination and unpolluted category by Pb, Cd, Cu, Zn, and Ni, while PAH content also still lower compared to sediment quality guideline.